Effects of technical training in functional asymmetry of lower limbs in young soccer players - José Guilherme; Júlio Garganta; Amândio Graça; André Seabra (Universidade Federal de Santa Catarina, 2015)
The functional asymmetry of the lower limbs has been considered an important factor in the performance of soccer players. In this sense, the purpose of this study was to examine the effects of specific technical training for non-preferred foot on its utilization rate during the game; and to investigate if interruption of a technical training programme for the non-preferred foot influences its utilization rate during the game. Fifty young soccer players were randomly divided into two groups: G1 (n=26, 9.50±1.04 years) and G2 (n=24, 9.58±1.02 years). At the beginning of the first 4 months, each player's use of both feet during the game was assessed. The study lasted eight months divided into two periods of four months. In the first training period G1 was subjected to a technical training programme directed to the non-preferred foot, while G2 had no constraints on the use of both feet. At the end of the 4th month the two groups were newly assessed. During the second training period G1 and G2 reversed the training programmes. After the 8 months of training the evaluation of the utilization rate of both feet during small-side games was again performed. The main conclusions of the study were: (i) the technical training of the non-preferred foot allowed significant increases in its utilization rate during small-sided games; (ii) the interruption of such training partially reversed this effect. Thus, technical training for the non-preferred foot should be systematically performed in order to maintain the positive effects induced over functional asymmetry.